PERAN INFLUENCER MARKETING DALAM MENINGKATKAN PENJUALAN PRODUK DI E-COMMERCE - Fikry Haikal; Laura Natasya Saragih; Nanda Meyshinta; Nurbaiti Nurbaiti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study examines the role of influencer marketing in enhancing product sales in e-commerce, focusing on the increasing use of social media that influences consumer behavior. The objective is to explore the impact of influencer marketing strategies on purchasing decisions. A descriptive qualitative approach was employed, analyzing relevant literature from various sources. The findings indicate that influencer marketing not only increases brand awareness but also builds consumer trust through authentic interactions. Carefully selected influencers can reach a broader audience and create a positive impact on product sales. The conclusion emphasizes the importance of choosing influencers that align with the target market characteristics. Recommendations for companies include considering market segmentation and the influencer's reputation in their marketing strategies to maximize sales potential and build long-term relationships with consumers.